Endovascular Surgery and Devices (Springer Singapore, 2018)
This book provides a systematic description of fundamental knowledge, application methods, and management issues about the clinical application of endovascular surgery and device. It is organized as the three parts. Part 1 introduces the development background of endovascular device and its knowledge hierarchy, and gives an overview on classification, structure, shape, and characteristics of the above device. Part 2 is based on a large number of clinical practices. It firstly summarizes the basic operation skills and conventional methods of endovascular device, and then exemplifies the application scheme of special device for complex cases. Part 3 discusses the management theory and methods of endovascular device in clinical application, puts forward the agile supply chain management model and autonomous intelligent decision-making method of device supply and cooperation management for clinical surgery, and designs its managerial system and guides. This book provides comprehensive and professional knowledge, advanced theory, and referential methods for clinical application and management of endovascular surgery and device. It is a useful guide for the clinical practice in specialized study and professional training in endovascular surgery, and provides the methods of neuro-management and smart medical service for patients.